Distinct CD4−CD8− (Double-Negative) Memory T-Cell Subpopulations Are Associated With Indeterminate and Cardiac Clinical Forms of Chagas Disease - Passos, Livia Silva Araújo; Koh, Carolina Cattoni; Magalhães, Luísa Mourão Dias; Nunes, Maria do Carmo Pereira; Gollob, Kenneth John; Dutra, Walderez Ornelas (Frontiers in Immunology, 2021)
CD4-CD8- (double-negative, DN) T-cells are critical orchestrators of the cytokine network associated with the pathogenic inflammatory response in one of the deadliest cardiomyopathies known, Chagas heart disease, which is caused by Trypanosoma cruzi infection. Here, studying the distribution, activation status and cytokine expression of memory DN T-cell subpopulations in Chagas disease patients without cardiac involvement (indeterminate form – IND) or with Chagas cardiomyopathy (CARD), we report that while IND patients displayed a higher frequency of central memory, CARD had a high frequency of effector memory DN T-cells. In addition, central memory DN T-cells from IND displayed a balanced cytokine profile, characterized by the concomitant expression of IFN-gamma and IL-10, which was not observed in effector memory DN T-cells cells from CARD. Supporting potential clinical relevance, we found that the frequency of central memory DN T-cells was associated with indicators of better ventricular function, while the frequency of effector memory DN T-cells was not. Importantly, decreasing CD1d-mediated activation of DN T-cells led to an increase in IL-10 expression by effector memory DN T-cells from CARD, restoring a balanced profile similar to that observed in the protective central memory DN T-cells. Targeting the activation of effector memory DN T-cells may emerge as a strategy to control inflammation in Chagas cardiomyopathy and potentially in other inflammatory diseases where these cells play a key role.